Selective inhibition of tumor growth by clonal NK cells expressing an ErbB2/HER2-specific chimeric antigen receptor - Schönfeld, Kurt; Holtgreve-Grez, Heidi; Jauch, Anna; Schmidt, Manfred (Molecular therapy, 2015)
Natural killer (NK) cells are an important effector cell type for adoptive cancer immunotherapy. Similar to T cells, NK cells can be modified to express chimeric antigen receptors (CARs) to enhance antitumor activity, but experience with CAR-engineered NK cells and their clinical development is still limited. Here, we redirected continuously expanding and clinically usable established human NK-92 cells to the tumor-associated ErbB2 (HER2) antigen. Following GMP-compliant procedures, we generated a stable clonal cell line expressing a humanized CAR based on ErbB2-specific antibody FRP5 harboring CD28 and CD3ζ signaling domains (CAR 5.28.z). These NK-92/5.28.z cells efficiently lysed ErbB2-expressing tumor cells in vitro and exhibited serial target cell killing. Specific recognition of tumor cells and antitumor activity were retained in vivo, resulting in selective enrichment of NK-92/5.28.z cells in orthotopic breast carcinoma xenografts, and reduction of pulmonary metastasis in a renal cell carcinoma model, respectively. γ-irradiation as a potential safety measure for clinical application prevented NK cell replication, while antitumor activity was preserved. Our data demonstrate that it is feasible to engineer CAR-expressing NK cells as a clonal, molecularly and functionally well-defined and continuously expandable cell therapeutic agent, and suggest NK-92/5.28.z cells as a promising candidate for use in adoptive cancer immunotherapy.